Westonci.ca is the Q&A platform that connects you with experts who provide accurate and detailed answers. Connect with professionals on our platform to receive accurate answers to your questions quickly and efficiently. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.

solve the equations. 13x - 6y = 22x= y + 6x=y=

Sagot :

[tex]\begin{gathered} 13x-6y=22\ldots\ldots(1) \\ x=y+6\ldots.\mathrm{\cdot}.(2) \\ \text{Substitute equation (2) into equation (1).} \\ 13(y+6)-6y=22 \\ 13y+78-6y=22 \\ 7y+78=22 \\ 7y=22-78 \\ 7y=-56 \\ y=-8 \\ Now,\text{ from equation (2)} \\ x=-8+6 \\ x=-2 \end{gathered}[/tex]